Hierarchical hollow nanofiber networks for high-performance hybrid direct carbon fuel cells. Issue 33 (8th August 2017) - Liu, Jia; Yuan, Hong; Qiao, Jinshuo; Feng, Jie; Xu, Chunming; Wang, Zhenhua; Sun, Wang; Sun, Kening
Abstract : Hierarchical, hollow nanofibers of Ce0.6 Mn0.3 Fe0.1 O2 were designed as an efficient anode for hybrid direct carbon fuel cells, which displayed superior electrochemical performance. Abstract : Herein, we demonstrated a new strategy for the development of Ce0.6 Mn0.3 Fe0.1 O2 hierarchically structured porous hollow nanofibers tailored as efficient anodes for hybrid direct carbon fuel cells. The cell based on the as-optimized anode delivered an excellent electrochemical performance and achieved a good long-term stability.